REKONSTRUKSI KONSEP KAFA'AH DALAM PERNIKAHAN: IMPLIKASI PENDIDIKAN, STATUS SOSIAL EKONOMI, DAN LATAR BELAKANG BUDAYA TERHADAP KESETARAAN DALAM KEMITRAAN - Akbar, Ahmad Rozai (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2025)
This study re-examines the concept of Kafa'ah in Islamic marriage which has been oriented towards equality of religion, lineage, and economy, but ignores the factors of education, socio-economic status, and culture that influence the implementation of society. The purpose of the study is to explore the relationship between these three factors and Kafa'ah, identify the impact of conceptual reconstruction on partnership equality, and the role of women's empowerment in determining the criteria for Kafa'ah. The library method with content analysis was carried out through a review of literature, journals, and normative sources of Islamic family law. The data shows that education is a new criterion for Kafa'ah in urban communities, while socio-economic hierarchy is still dominant in traditional communities. The conclusion states that inclusive reconstruction of Kafa'ah can improve gender equality and the welfare of couples, while strengthening women's position in determining their choice of partners independently. These results have implications for the development of regulations and public education to encourage more egalitarian marriage practices